2021
DOI: 10.15547/bjvm.2019-0046
|View full text |Cite
|
Sign up to set email alerts
|

Unique report of two Sarcocystis species from Egyptian domestic chicken (Gallus gallus) – new host and locality

Abstract: Sarcocystis is an intracellular protozoan parasite in the phylum Apicomplexa. It is widely distributed all over the world. There are scarce reports about chicken Sarcocystis. From February 2016 to January 2018, a total number of 630 chicken carcasses, intestines and viscera were collected from different chicken markets in Menoufia and Gharbia Governorates, Middle region of the Nile Delta, Egypt and carefully inspected. Macroscopic and microscopic cysts of Sarcocystis spp. were found in the intestinal wall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…However, there are no studies reporting the detection of antibodies against Sarcocystis in chickens. The molecular prevalence of Sarcocystis in village chickens in the current study was higher than that reported in free-ranging chickens in Egypt (0.79%) through macroscopic and microscopic examination of the heart, liver, lung, and intestines (Galila et al, 2021). However, a much higher prevalence was reported in free-range chickens from China (42.4%) following microscopic examinations of skeletal and heart muscles (Pan et al, 2020).…”
Section: Discussioncontrasting
confidence: 80%
“…However, there are no studies reporting the detection of antibodies against Sarcocystis in chickens. The molecular prevalence of Sarcocystis in village chickens in the current study was higher than that reported in free-ranging chickens in Egypt (0.79%) through macroscopic and microscopic examination of the heart, liver, lung, and intestines (Galila et al, 2021). However, a much higher prevalence was reported in free-range chickens from China (42.4%) following microscopic examinations of skeletal and heart muscles (Pan et al, 2020).…”
Section: Discussioncontrasting
confidence: 80%